A DESCRIPTIVE STUDY ON THE CONJUNTIONS' MASTERY OF THE SECOND YEAR STUDENTS OF SMA MUHAMMADIYAH 03 KENDAL IN THE ACADEMIC YEAR 2005/2006 - ALFATHON, MUHAMMAD IBNU HAJAR (2007)
This research is aimed at describing the students’ mastery on conjunctions and finding the students’ difficulties. The mastery of conjunction is essential for students in constructing grammatically acceptable sentences. The test is used as the instrument in collecting the data to be analyzed, while this research uses descriptive quantitative method. The samples are the students of SMA Muhammadiyah 03 Kendal. The number of samples is 40 students. The writer uses random sampling in which he randomly chooses 40 students from the total 156 students as the sample by using lottery. The writer uses a percentage correction technique for getting the percentage of the correct answers to measure the students’ ability in using conjunctions in sentence. Based on the result of the data analysis that has been done, the writer knows that the students can correctly answer the test 62,38% from the total correct answers. There are 6 students (15%) who belong to very good category. There are 16 students (40%) who are in the good category. There are 14 students (35%) who belong to fair category and 4 students (10%) who belong to bad category. It is known that most students belong to the good level. It means that the students’ English conjunctions mastery of the second year students of SMA Muhammadiyah 03 Kendal is good (62.38%). However, the students have difficulties in using coordinating conjunction (29,28%), subordinating conjunction (32,20%), correlation conjunction (61,87%).